2014
DOI: 10.3109/13697137.2013.876618
|View full text |Cite
|
Sign up to set email alerts
|

Guizhi Fuling capsule, an ancient Chinese formula, attenuates endometriosis in rats via induction of apoptosis

Abstract: These results indicate that the GZFL capsule can induce apoptosis of endometriotic cells and inhibit cell proliferation and metastasis of endometriotic cells through the mitochondrial apoptotic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Metabonomic technology has been considered as an efficient tool for diagnosis and evaluation of TCM therapy, because its systemic features are consistent with the comprehensive therapeutic efficacies and mechanisms of TCM action (Su et al, ; Tan et al, ; Tan et al, ). GFC is a historically documented formula for prevention of PD with no adverse effects (Hu et al, ; Lan et al, ). In our study, an RP‐UPLC‐MS coupled with HILIC‐UPLC‐MS‐based metabonomics approach was used to analyze metabolite profiling before and after treatment by GFC in PD rats, as well as the possible intervention mechanism of GFC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabonomic technology has been considered as an efficient tool for diagnosis and evaluation of TCM therapy, because its systemic features are consistent with the comprehensive therapeutic efficacies and mechanisms of TCM action (Su et al, ; Tan et al, ; Tan et al, ). GFC is a historically documented formula for prevention of PD with no adverse effects (Hu et al, ; Lan et al, ). In our study, an RP‐UPLC‐MS coupled with HILIC‐UPLC‐MS‐based metabonomics approach was used to analyze metabolite profiling before and after treatment by GFC in PD rats, as well as the possible intervention mechanism of GFC.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf (Poria), Paeonia lactiflora Pall (Herbaceous peony), Paeonia suffruticosa andrews (Moutan Cortex) and Amygdalus persica L. (Persicae Semen) (Liu et al, ). GFC has been widely applied in the clinical prevention and treatment of dysmenorrheal, uterine fibroids, endometriosis, ovarian cysts and pelvic inflammatory disease, which are considered to be caused by the disharmony patterns of blood stasis in TCM (Hu et al, ; Li et al, ; Yao & Shulan, ). Our previous studies have shown that GFC could significantly inhibit the expression of cyclooxygenase‐2 and oxytocin receptor, and reduce the level of prostaglandin F 2a (PGF 2a ), intracellular Ca 2+ and NO in uterine tissue of oxytocin‐induced rats (Lan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It consists of five herbs (Cinnamomi ramulus, W. extensa, P. suffruticosa Andrews, P. persica, and P. lactiflora) [17,18]. GBH has been used mainly for treating primary dysmenorrhoea, uterine myoma [19], and climacteric symptoms such as hot flashes [18]. A phase II trial to assess the efficacy of GBH (TU-025) Tsumura & Co (Tokyo, Japan) for hot flash management was conducted in the United States; however, the results did not show significant clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported that GZFLC attenuated endometriosis in rats via induction of apoptosis and inhibition of cell proliferation and metastasis [19]. In terms of its anticancer effect, this phenomenon was also found in human hepatocellular carcinoma [20, 21], bladder cancer [22], and cervical cancer [23].…”
Section: Discussionmentioning
confidence: 99%